Pengaruh Penggunaan Model Pembelajaran Savi Terhadap Aktivitas Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Di SMP Negeri 1 Secanggang - Zulvita Nada; Juli Maini Sitepu (Al-Ulum: Jurnal Pendidikan Islam, 2023)
This study aims to determine the effect of using the SAVI learning model on student learning activities in Islamic Religious Education subject at SMP Negeri 1 Secanggang. The research method used is a quantitative type of quasi-experimental research. The subjects of this study were students of class VIII-6 as the experimental class and class VIII-7 as the control class. Data collection techniques used are questionnaires (questionnaire), observation and documentation. Data analysis used is t-test. Based on the results of data analysis using the t-test, the Sig.(2-tailed) value is lower than 0.05 (0.000 <0.05) so that Ho is rejected and Ha is accepted. This shows that there are differences in student learning activities between using the SAVI learning model and conventional methods so that it can be concluded that the use of the SAVI learning model affects student learning activities in Islamic Religious Education subject at SMP Negeri 1 Secanggang.